2024
DOI: 10.1002/prep.202300035
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of nitrocellulose with different nitrogen content

Xiang Cao,
Fengqiang Nan,
Yiying Zheng
et al.

Abstract: Research on the hygroscopic behavior of NC is essential because it affects the mechanical properties, combustion properties, and safe storage of NC‐based products. In this study, Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), and scanning electron microscopy (SEM) are used to characterize the chemical structure, crystal structure, and microscopic morphology of NC, respectively. The moisture adsorption isotherms of NC fibers with different nitrogen content are determined by dynamic vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…As the degree of substitution increased, the nitrogen content of the CN samples (Table 2) also increased, while the intensity of hydroxyl peaks became less pronounced. This observation aligns with previous studies reported in [8,11,37,57,58]. Specifically, the CN NA + MC samples exhibited a lower hydroxyl intensity compared to the CN MA samples, consistent with their higher nitrogen content.…”
Section: Resultssupporting
confidence: 92%
“…As the degree of substitution increased, the nitrogen content of the CN samples (Table 2) also increased, while the intensity of hydroxyl peaks became less pronounced. This observation aligns with previous studies reported in [8,11,37,57,58]. Specifically, the CN NA + MC samples exhibited a lower hydroxyl intensity compared to the CN MA samples, consistent with their higher nitrogen content.…”
Section: Resultssupporting
confidence: 92%